Prevalensi Platyhelminthes pada Rusa Tutul (Axis axis) di Taman Hutan Kota Langsa, Aceh - Nur Ramadani; Sri Jayanthi; Teuku Hadi Wibowo Atmaja (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Spotted deer (Axis axis) is one of the protected deer species in Indonesia. Spotted deer have been listed on the IUCN Red List of Threatened Species, with a conservation status of LC (Least Concern). In the conservation of spotted deer, failure often occurs due to diseases that arise due to conditions that are not in accordance with their natural habitat. One of the main problems is parasitic infections. This study aims to determine the type, prevalence and intensity of Platyhelminthes in spotted deer (Axis axis) in Langsa City Forest Park, Aceh. The samples used were the feces of 13 spotted deer in Langsa City Forest Park, Aceh. The type of research is descriptive quantitative with observation methods. Data analysis used is a description of prevalence and intensity values. The results showed that there were 3 types of Platyhelminthes, namely Schistosoma intercalatum and Schistosoma mansoni from the Schistosomatidae family, Strigeatida order, Trematoda class and Taenia sp. from the Taeniidae family, Cyclopphyllidea order, Cestoda class. Schistosoma intercalatum has a prevalence of 23.07% (frequent) and intensity of 1.3 (light parasite), Schistosoma mansoni has a prevalence of 15.38% (frequent) and intensity of 1 (light parasite) and Taenia sp. has a prevalence of 38.46% (general) and intensity of 1.4 (light parasite).